Methamphetamine facilitates pulmonary and splenic tissue injury and reduces T cell infiltration in C57BL/6 mice after antigenic challenge - Adriana C. Hernandez-Santini (Nature Portfolio, 2021)
Abstract Methamphetamine (METH) is a strong addictive central nervous system stimulant. METH abuse can alter biological processes and immune functions necessary for host defense. The acquisition and transmission of HIV, hepatitis, and other communicable diseases are possible serious infectious consequences of METH use. METH also accumulates extensively in major organs. Despite METH being a major public health and safety problem globally, there are limited studies addressing the impact of this popular recreational psychostimulant on tissue adaptive immune responses after exposure to T cell dependent [ovalbumin (OVA)] and independent [lipopolysaccharide (LPS)] antigens. We hypothesized that METH administration causes pulmonary and splenic tissue alterations and reduces T cell responses to OVA and LPS in vivo, suggesting the increased susceptibility of users to infection. Using a murine model of METH administration, we showed that METH causes tissue injury, apoptosis, and alters helper and cytotoxic T cell recruitment in antigen challenged mice. METH also reduces the expression and distribution of CD3 and CD28 molecules on the surface of human Jurkat T cells. In addition, METH decreases the production of IL-2 in these T-like cells, suggesting a negative impact on T lymphocyte activation and proliferation. Our findings demonstrate the pleotropic effects of METH on cell-mediated immunity. These alterations have notable implications on tissue homeostasis and the capacity of the host to respond to infection.